Mifepristone Increases Life Span of Virgin Female Drosophila on Regular and High-fat Diet Without Reducing Food Intake - Landis, Gary N.; Hilsabeck, Tyler A. U.; Bell, Hans S.; Ronnen-Oron, Tal; Wang, Lu; Doherty, Devon V.; Tejawinata, Felicia I.; Erickson, Katherine; Vu, William; Promislow, Daniel E. L.; Kapahi, Pankaj; Tower, John (Frontiers in Genetics, 2021)
Background: The synthetic steroid mifepristone is reported to have anti-obesity and anti-diabetic effects in mammals on normal and high-fat diets (HFD). We previously reported that mifepristone blocks the negative effect on life span caused by mating in female Drosophila melanogaster. Methods: Here we asked if mifepristone could protect virgin females from the life span-shortening effect of HFD. Mifepristone was assayed for effects on life span in virgin females, in repeated assays, on regular media and on media supplemented with coconut oil (HFD). The excrement quantification (EX-Q) assay was used to measure food intake of the flies after 12 days mifepristone treatment. In addition, experiments were conducted to compare the effects of mifepristone in virgin and mated females, and to identify candidate mifepristone targets and mechanisms. Results: Mifepristone increased life span of virgin females on regular media, as well as on media supplemented with either 2.5% or 5% coconut oil. Food intake was not reduced in any assay, and was significantly increased by mifepristone in half of the assays. To ask if mifepristone might rescue virgin females from all life span-shortening stresses, the oxidative stressor paraquat was tested, and mifepristone produced little to no rescue. Analysis of extant metabolomics and transcriptomics data suggested similarities between effects of mifepristone in virgin and mated females, including reduced tryptophan breakdown and similarities to dietary restriction. Bioinformatics analysis identified candidate mifepristone targets, including transcription factors Paired and Extra-extra. In addition to shortening life span, mating also causes midgut hypertrophy and activation of lipid metabolism regulatory factor SREBP. Mifepristone blocked the increase in midgut size caused by mating, but did not detectably affect midgut size in virgins. Finally, mating increased activity of a SREBP reporter in abdominal tissues, as expected, but reporter activity was not detectably reduced by mifepristone in either mated or virgin females. Conclusion: Mifepristone increases life span of virgin females on regular and HFD without reducing food intake. Metabolomics and transcriptomics analyses suggest some similar effects of mifepristone between virgin and mated females, however reduced midgut size was observed only in mated females. The results are discussed regarding possible mifepristone mechanisms and targets.